2010
DOI: 10.1016/j.pneurobio.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The nicotinic acetylcholine receptor CHRNA5/A3/B4 gene cluster: Dual role in nicotine addiction and lung cancer

Abstract: More than 1 billion people around the world smoke, with 10 million cigarettes sold every minute. Cigarettes contain thousands of harmful chemicals including the psychoactive compound, nicotine. Nicotine addiction is initiated by the binding of nicotine to nicotinic acetylcholine receptors, ligand-gated cation channels activated by the endogenous neurotransmitter, acetylcholine. These receptors serve as prototypes for all ligand-gated ion channels and have been extensively studied in an attempt to elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 240 publications
(349 reference statements)
1
67
0
Order By: Relevance
“…It also identifies key residues such as Asn 9 , Asn 11 , and Asn 12 involved in toxin-receptor interaction. This information will be valuable in the design and development of potent, ␣3␤4-selective drugs to treat lung cancer and nicotine addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also identifies key residues such as Asn 9 , Asn 11 , and Asn 12 involved in toxin-receptor interaction. This information will be valuable in the design and development of potent, ␣3␤4-selective drugs to treat lung cancer and nicotine addiction.…”
Section: Discussionmentioning
confidence: 99%
“…8). Two studies identified tobacco-specific nitrosamines as potent nAChR agonists and inhibitors of cancer cell apoptosis (9). In addition, genome-wide studies identified associations between lung cancer and several single nucleotide polymorphisms within the gene cluster encoding the ␣3, ␣5, and ␤4 nAChR subunits (10).…”
mentioning
confidence: 99%
“…Drug discrimination assays have been used in attempts to isolate the receptor that is most relevant to nicotine's interoceptive effects, and several lines of evidence indicate that these are also mediated through the ␣4␤2 subtype of the nAChR (for review, see Smith and Stolerman, 2009). Nevertheless, genetic studies in particular have implicated other nicotinic receptor subtypes, such as the ␣3, ␣5, ␣6, and ␤4 subunits, in the abuse liability of nicotine (Improgo et al, 2010;Sherva et al, 2010;Russo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CHRNB4 contains a 3′ enhancer element involved in this combined regulation. 47,48 The rs3813567 major T allele was reported to be associated with risk for smoking, 49 but those results were not based on a selegiline clinical trial. Our results indicate that during selegiline treatment it was the C minor allele that was over-represented among those not abstinent.…”
Section: Discussionmentioning
confidence: 99%